Thrombus Inhibition and Neuroprotection for Ischemic Stroke Treatment through Platelet Regulation and ROS Scavenging. (7th November 2022) - Ye, Hongbo; Ma, Zhifang; Liu, Lei; Zhang, Tianci; Han, Qiaoyi; Xiang, Zehong; Xia, Yu; Ke, Yue; Guan, Xinghua; Shi, Qiang; Ataullakhanov, Fazly I.; Panteleev, Mikhail
Abstract: Ischemic stroke is caused by cerebrovascular stenosis or occlusion. Excessive reactive oxygen species (ROS) are the focus‐triggering factor of irreversible injury in ischemic regions, which result in harmful cascading effects to brain tissue, such as inflammation and microthrombus formation. In the present work, we designed nanodelivery systems (NDSs) based on MnO2 loaded with Ginkgolide B (GB) for restoring the intracerebral microenvironment in ischemic stroke, such as ROS scavenging, O2 elevation, thrombus inhibition and damage repair. GB can activate the endogenous antioxidant defense of cells by enhancing the nuclear factor‐E2‐related factor 2 (Nrf2) signalling pathway, thus protecting brain tissue from oxidative damage. However, the blood–brain barrier (BBB) is also a therapeutic obstacle for the delivery of these agents to ischemic regions. MnO2 nanoparticles have an inherent BBB penetration effect, which enhances the delivery of therapeutic agents within brain tissue. MnO2, with mimicking enzymatic activity, can catalyze the decomposition of overproduced H2 O2 in the ischemic microenvironment to O2, meanwhile releasing platelet‐antagonizing GB molecules, thus alleviating cerebral hypoxia, oxidative stress damage, and microthrombus generation. This study may provide a promising therapeutic route for regulating the microenvironment of ischemic stroke through a combined function of ROS scavenging, microthrombus inhibition, and BBB penetration. Abstract : After intravenous injection, MnO2 ‐Ginkgolide B (GB) nanoparticles could cross the blood–brain barrier into brain tissue. In a murine model of ischemic stroke, MnO2 can consume reactive oxygen species, produce oxygen, and work together with the loaded platelet antagonist GB to exert antithrombotic, antioxidant, and neuroprotective effects through activation of the Nrf2 signaling pathway.